Perancangan Sistem Efisiensi Penggunaan Energi Listrik Menggunakan Sensor Gerak dan Sensor Arus - Sarmayanta Sembiring; Hadir kaban; Rido Zulfahmi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Efficiency system in using electrical energy has been designed using a PIR motion sensor, current sensor SCT-013-030, infrared LED and relay with a controller using Arduino Uno. The system is designed to turn off electronic equipment such as air conditioners, projectors and lights automatically as a solution from users forgetting to turn off electronic equipment when it is no longer in use. The experimental results show that the system has been running well, where the system can detect no movement for a predetermined time by using a PIR motion sensor. Detection of electronic equipment using sensors SCT-013-030 has been able to distinguish the state of the equipment whether it is ON or OFF based on differences in sensor output data that is read by the Arduino analog port. Sensor data when detecting the lamp when OFF is average = 1.333 while the mini projector and TV when off the average sensor data value = 1.667. The average current sensor data when detecting lights when ON = 5,333, mini projector = 8,333 and TV = 11,333. Overall the system designed has been able to turn off the equipment that is still active when the sensor does not detect any human movement during a predetermined time